(untitled) (Revista Lusófona de Educação, 2025)
This article is the result of an ongoing European research project, that aims at recognizing policies and practices, to reduce failure and early school leaving, based on scientific evidence. Hence, we will discuss two case studies, which took place in two school clusters, in the Greater Porto region, which were considered particularly relevant to identifying successful practices, as a response to challenging educational contexts. The methodology used, of an eminently qualitative nature, includes interviews with teachers, technicians and education staff, and the dynamization of focus groups with students. The results discussed in this article make it possible to triangulate the students’ perspectives with those of teachers and other professionals, enhancing the construction of successful students’ profiles, the roles attributed to well-being in these profiles, valuing the recognition of students’ involvement in the learning process. The results emphasise the importance of studying pupils’ wellbeing, since pupils’ success seems to be directly related to their wellbeing, and it is increasingly recommended that wellbeing be considered as a key element of that success. Wellbeing promotion should also be involved in the construction of the school as a relational and inclusive space. Keywords: Youth; Inclusion; Social Justice; Well-being; School